Albania : 2010 Article IV Consultation; Staff Report; Staff Statement; Public Information on the Executive Board Discussion; and Statement by the Executive Director for Albania. (IMF Staff Country Reports; Country Report ;, 2010)
Albania enjoyed strong growth with comparatively benign external vulnerabilities before the crisis. Monetary policy provided timely support, and the exchange rate functioned as a shock absorber. However, policy buffers are now exhausted and must be rebuilt. Fiscal tightening has to be quickly effected. Medium-term fiscal policy should be governed by a credible and monitorable fiscal rule. The Albanian economy has to broaden its sources of growth and strengthen competitiveness. Sound macroeconomic statistics are essential for competent policy making and investor confidence.